(untitled) (Research, Society and Development, 2022)
The assessment of higher education courses by graduates contributes to improvements in Pedagogical Projects, learning management and training of future professionals. This paper presents the validation of an instrument for assessment engineering courses by graduates. The validation was carried out by eleven specialists from different regions of Brazil, professors with a PhD in engineering, interested in the implementation of the Curriculum Guidelines for Engineering in Brazil. The instrument had implemented suggestions, such as: title; items about gender and color; skills and competences; corrections, substitutions, deletions and additions of terms and expressions in some items. According to specialists, this instrument is of relevance and could be applied to different engineering institutions in the country.